Pengaruh Latihan Kekuatan Terhadap Kemampuan Smash Dalam Permainan Bola Voli Pada Siswa SMP Negeri 10 Kota Palopo - Hidayat Nurwahid; Rasyidah Jalil; Marhani Marhani (Universitas Hamzanwadi, 2025)
Smash ability in volleyball is greatly influenced by physical condition, especially the strength of the arm, leg, and core muscles. However, initial observations at SMP Negeri 10 Kota Palopo showed that most students still had difficulty performing smashes due to weak muscles. This study aimed to determine the effect of strength training on improving volleyball smash ability. The method used was an experiment with a one-group pretest-posttest design. The sample consisted of 30 students selected at random. The research instrument was a smash skill test that measured the accuracy and technique of the hit, with a validity of 0.85 and reliability of 0.84. The treatment given was a strength training program consisting of push-ups, squat jumps, and back-ups, which was carried out over 16 sessions with the application of the principle of progressive overload. The data were analyzed using the Shapiro-Wilk normality test, homogeneity test, and paired t-test at a significance level of 0.05. The results showed an increase in the average smash skill score from 18.03 (pretest) to 22.23 (posttest), with an increase of 4.20 points. The hypothesis test produced a significance value of 0.000 (<0.05) and a Cohen's d effect size value of 2.67 (very large effect category). Thus, strength training proved to be effective and had a significant effect on improving volleyball smash ability.